Pengaruh Komunikasi Dan Keselamatan Kerja Terhadap Kinerja Karyawan - Alfadilla Khunaini; Indah Rizki Maulia; Tiara Putri Fadyanti; Widya Meliawati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
The influence of Communication and work safety on employee performance is a scientific literature review article. The purpose of writing this article is to build a hypothesis on the influence or role between variables that will be used in further research, within the scope of Human Resource Management. The article writing method is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. Qualitative descriptive analysis. The results of this article are: 1) Communication influences employee performance; 2) Work safety influences employee performance